Omental and pleural milky spots: different reactivity patterns in mice infected with Schistosoma mansoni reveals coelomic compartmentalisation - Mônica S Panasco; Marcelo Pelajo-Machado; Henrique Leonel Lenzi (Memorias do Instituto Oswaldo Cruz, 2010)
In vertebrate animals, pleural and peritoneal cavities are repositories of milky spots (MS), which constitute an organised coelom-associated lymphomyeloid tissue that is intensively activated by Schistosoma mansoni infection. This study compared the reactive patterns of peritoneal MS to pleural MS and concluded from histological analysis that they represent independent responsive compartments. Whole omentum, lungs and the entire mediastinum of 54 S. mansoni-infected mice were studied morphologically. The omental MS of infected animals were highly activated, modulating from myeloid-lymphocytic (60 days of infection) to lymphomyeloid (90 days of infection) and lymphocytic or lymphoplasmacytic (160 days of infection) types. The non-lymphoid component predominated in the acute phase of infection and was expressed by monocytopoietic, eosinopoietic and neutropoietic foci, with isolated megakaryocytes and small foci of late normoblasts and mast cells. Nevertheless, pleural or thoracic MS of infected mice were monotonous, consisting of small and medium lymphocytes with few mast and plasma cells and no myeloid component. Our data indicate that compartmentalisation of the MS response is dependent on the lymphatic vascularisation of each coelomic cavity, limiting the effects or consequences of any stimulating or aggressive agents, as is the case with S. mansoni infection.